INTEGRATING LOCAL WISDOM INTO DIGITAL STORYBOOKS: AN INNOVATIVE LITERACY APPROACH TO ENHANCING ELEMENTARY STUDENTS' READING INTEREST: English - Jepri Yansyah; Bernadus Wahyudi Joko Santoso; Haryadi (Jurnal Cakrawala Pendas, 2026)
The low level of reading interest among elementary school students in the digital era has become a significant challenge in literacy development, particularly due to the dominant use of gadgets for entertainment rather than educational purposes. This study aims to analyze the effectiveness of digital storybooks based on local wisdom in improving students’ reading interest. The research employed a quantitative approach using a quasi-experimental design with a one-group pretest-posttest model. The participants were fourth-grade elementary school students, and the instrument used was a reading interest questionnaire covering indicators of interest, frequency, and motivation to read. Data were analyzed using descriptive statistics and a paired sample t-test. The results revealed a significant improvement in students’ reading interest after the implementation of local wisdom-based digital storybooks, as indicated by the increase in mean scores and the shift in reading interest categories from low to high. Statistically, the significance value obtained was less than 0.05, confirming that the intervention had a significant effect. This improvement is attributed to the interactive, visual, and contextual nature of the media, as well as the integration of local cultural values that make learning more meaningful. Therefore, local wisdom-based digital storybooks are recommended as an effective and relevant innovation for literacy learning in elementary schools in the digital era.